Correlation of anemia status with worsening bowel damage as measured by Lémann Index in patients with Crohn's disease. Issue 6 (June 2016) - Bhagya Rao, Bhavana; Koutroubakis, Ioannis E.; Rivers, Claudia Ramos; Regueiro, Miguel; Swoger, Jason; Schwartz, Marc; Baidoo, Leonard; Hashash, Jana; Barrie, Arthur; Dunn, Michael A.; Binion, David G.
Abstract: Background: There is evidence that anemia in Crohn's disease (CD) is a predictor of disease severity. Aim: To evaluate if patterns of anemia over time showed correlation with aggressive disease trajectory, as characterized by change in Lémann Index (LI), which is a metric that quantifies bowel damage. Methods: CD patients with 5 year (y) follow-up from a prospective registry were included. LI was calculated from the first (LI1) and last (LI2) clinical encounters. The change in score (LI2–LI1) or the Delta LI (DLI) was recorded. Patterns of anemia, healthcare utilization and disease activity scores were analyzed. Results: A total of 389 CD patients with 5 y follow-up formed the study population [median age 40 y (IQR: 31–53); 57.3% female; median disease duration 12 y (IQR: 6–20.5), overall surgical exposure 69%]. Patients with anemia had significantly higher LI1, LI2, DLI and also significantly higher healthcare utilization and indices of disease activity, than patients without anemia ( p < 0.001). CD patients with anemia for any duration during the study had OR of 2.15 (95% CI 1.29–3.57, p = 0.003) for worsening bowel damage over the 5 y. Conclusion: Based on a longitudinal analysis of CD patients, anemia status over time shows significant correlation with increasing Lémann index and aggressive disease trajectory.